Fertility index, flowering aspects and pomological traits on almond genotypes from different areas - Sottile F.; Monte M.; Omodei F.; Barbera G. (XIII GREMPA Meeting on Almonds and Pistachios, 2005)
Since 1997 an 'on farm' collection and evaluation orchard has been set up in Sicily in order to collect a large part of the vast almond germplasm. GF677 trees were planted in 1996 at 6x4 m and grafted with budsticks collected throughout the traditional almond growing areas of Sicily. Many cultivars native to different parts of Italy and of the world have also been included to compare the main aspects related to vegetative and reproductive behaviour. The aim of this paper was to carry out a preliminary evaluation work on some of the cultivars collected in order to describe their behavior in terms of flowering biology and nut traits.
13. Meeting of the Mediterranean Research Group for Almond and Pistachio, 2003/06/01-05, Mirandela (Portugal)